From Connectivity to Commitment: How Political Information Sources Shape Voter Participation in Bogor City and Regency - Anggraeni, Khori Aulia Ria; Permatasari, Olivia Devita; Widjaya, Mochammad Fahrezi Putra; Hawari, Muhammad Haikal; Yuandari, Wulan; Jayawinangun, Roni (International Journal of Business, Economics, and Social Development, 2025)
This research stems from declining public political participation in the 2024 Regional Elections (Pilkada) in Bogor City and Regency. Indonesia, one of the world's largest democracies, faces low civic engagement in the electoral process, which is influenced by literacy and access to political information. This study aims to identify the main sources of political information; assess the knowledge, interest, and political participation of voters; and compare political behavior between urban and sub-urban areas. This research uses a quantitative explanatory approach with a survey method on 402 respondents from the Final Voter List (DPT) for the 2024 Pilkada. Descriptive tests and difference tests (t-test and Mann-Whitney. The results show that social media is the dominant source of political information in both areas, with the highest usage compared to conventional media, such as television and newspapers. Bogor City residents have more varied media consumption, indicating better digital literacy compared to Bogor Regency residents who rely more on social media. Political knowledge in both regions is relatively similar, but political interest and participation are higher in bogor. The difference tests showed significant differences emerge in participation and interest, with urban residents being more active in online and offline political activity. Overall, the study highlights that Indonesia’s increasingly digitalized democracy fosters broader information access but requires greater emphasis on digital literacy and civic education to transform online engagement into meaningful democratic participation. This study recommends strengthening digital political literacy through creative content, collaborating with digital platforms to counter disinformation, and establishing digital literacy agents at subdistrictrict level to encourage inclusive political engagement.